SPATIO-TEMPORAL VARIABILITY OF CARBOHYDRATE AND CHLOROPHYLL CONTENT IN THE COFFEE CANOPY - Santini, Paula Tristão; Almeida, Lorena Gabriela; Souza, Kamila Rezende Dázio de; Barbosa, João Paulo Rodrigues Alves Delfino; Alves, José Donizeti (Coffee Science - ISSN 1984-3909, 2019)
The spatial variability of the total chlorophyll content and carotenoids content, starch and soluble sugars of coffee canopy were mapped throughout the day. Therefore, evaluations were carried out in a ‘Catuaí Vermelho’ coffee plant with 1.7 meters height. A vertical gradient (from the apex to the base of the plant canopy) and a horizontal gradient (plagiotropic branches) were established to analyze different positions of the canopy. Thus, in the vertical direction, four heights were analyzed in the plant: top, upper, middle and lower regions. In the horizontal gradient, the plagiotropic branches were divided into three parts: basal, median and apical. Collection of leaf samples was performed on the east and west sides of the canopy, at 9 a.m., totaling 24 collection points at each time. Higher content of photosynthetic pigments and concentration of sugars were observed in the western face and in the inner parts of the coffee tree. The content of chloroplast pigments and sugars of an individual coffee leaf diverge considerably from other leaves, which requires caution when scaling estimates at the global canopy level. The analysis of some punctual leaves does not serve to discriminate the overall dynamics of a canopy.